Predictors of outcome after childhood ischemic stroke at a referral neuroscience hospital in Bangladesh - Alam, Sarah; Saha, Narayan; Islam, Ariful; Sumi, Samsun Nahar; Hosain, Ahmed; Jasmine, Tahsina; Rahman, Sheikh Nashfiqur; Esteak, Tareq (International Journal of Research in Medical Sciences, 2024)
Background: Though stroke in the pediatric age group is not as common as in adults, it is now recognized as an important cause of morbidity and mortality in children. For proper management of childhood stroke, it is very important to know about the spectrum of clinical presentation, risk factors, and neuroimaging features that can affect the outcome following stroke. The aim of the study was to identify predictors of outcomes in children with ischemic stroke treated at a referral neuroscience hospital in Bangladesh. Methods: A one-year prospective cohort study was conducted at the department of pediatric neurology, national institute of neurosciences and hospital (NINS and H), Dhaka, from March 2021 to February 2022. It involved 42 consecutive pediatric ischemic stroke patients aged 1 month to 18 years. Post-operative outcomes were assessed clinically, biochemically, and with imaging at discharge, 1 month, and 6 months post-discharge using the PSOM scale. Statistical analysis was performed using SPSS version 23.0, with significance set at p<0.05. Results: In our pediatric ischemic stroke study (n=42), most patients (76.2%) were aged 1-5 years, with iron deficiency anemia (59.5%) as the predominant risk factor. Anterior circulation stroke was common (90.5%), and PSOM assessments showed 28.6% favorable outcomes at discharge, increasing to 76.2% at 6 months. Seizure, speech difficulty, altered consciousness, and CNS infection were linked to poorer outcomes (p<0.005). Conclusions: Childhood stroke poses significant morbidity, with variable neurological outcomes. Factors like seizure, speech difficulty, altered consciousness, and CNS infection predict poorer outcomes.